Strict Incentives and Strategic Uncertainty - Hans Carlsson; Philipp Christoph Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper proposes a comprehensive perspective on the question of self-enforcing solutions for normal form games. While this question has been widely discussed in the literature, the focus is usually either on strict incentives for players to stay within the proposed solution or on strategic uncertainty, i.e. robustness to trembles. The present approach combines both requirements in proposing the concept of robust sets, i.e. sets of strategy profiles which satisfy both strict incentives and robustness to strategic uncertainty. The result is a set valued solution, a variant of which is shown to exist for all finite normal form games.
Keywords: C72; 330; game theory; self-enforcing solution; strict incentives; strategic uncertainty